Concrete Pictorial Abstract (CPA) Method-Based Intervention to Improve Understanding of Two-Digit Addition Concepts in Children with Mathematics Learning Difficulties - Fatimah Hasibuan, Siti; Sutatminingsih, Raras; Maulina Ozar, Bania (ATTA`DIB, 2025)
Mathematics learning difficulties in elementary school children remain a critical issue due to their impact on cognitive development, academic readiness, and emotional regulation. This study emphasizes the importance of instructional approaches that align with children’s cognitive developmental stages, particularly for those who have not yet fully reached concrete operational thinking despite having adequate intellectual potential. This study aimed to describe the cognitive and affective profile of a child with mathematics learning difficulties and to analyze changes in conceptual understanding following the implementation of the Concrete–Pictorial–Abstract (CPA) approach in two-digit arithmetic. A qualitative case study design was employed, involving psychological assessment, observation of learning behavior, cognitive testing, error analysis, and a four-stage CPA intervention. Data were analyzed thematically to identify patterns of difficulty, thinking processes, and learning changes before and after the intervention. The findings showed an increase in calculation accuracy from 41.6% to 83%, accompanied by reduced mathematics anxiety, increased learning engagement, and the emergence of basic mental calculation strategies. Follow-up results indicated an 80% retention of skills, suggesting that the conceptual understanding developed through the CPA stages was relatively stable. Overall, this study highlights the role of a developmentally appropriate, concrete visual abstract learning sequence in supporting both cognitive and affective aspects of mathematics learning in children with specific learning difficulties. Further research is recommended to explore the application of this approach in broader educational contexts.